From preference to landscape sustainability: a bibliometric review of landscape preference research from 1968 to 2019 - Yang, Gaoyuan; Yu, Zhaowu; Zhang, Jinguang; Søderkvist Kristensen, Lone (Ecosystem health and sustainability, 2021)
Landscape preference (LP) studies highlight one of the most important issues of human-environment relationship, and their related publications have increased rapidly over the last two decades. However, there is no systematic review with a holistic understanding of this field.   here we applied a bibliometric approach to examine the evolution of LP research and identify its status and future prospects. We obtained 7,637 LP research publications from Web of Science core collection from 1968 to 2019 and analyzed the characteristics of publication outputs as well as performances in various countries and institutions. Besides, content keywords analysis was conducted to discover the drivers, focus, motivation, and trends of LP research. We found that 1) publications, subject categories, and active journals increased rapidly since the 2000s ; 2) the USA, England, and Australia are the leading countries in LP research, while China is starting to have some influence; 3) LP research is most closely linked to ecological and environmental studies, being developed by objective drivers, i.e., interactions with landscape change, and subjective motivations ; and 4) LP research is advancing the landscape sustainability science, integrating natural and social science together through ecosystem services. By comprehensively reviewing the evolution and prospect of LP research, we provide insights for further research in this field.